(untitled) (Research, Society and Development, 2020)
Motor coordination can be defined as the ability to efficiently control the degrees of freedom of the different body segments involved in movement, being a decisive factor for success in sports. Paralympic sport consists of a sport subfield, being one of the possible alternatives for the participation for people with disabilities in sports. Among the various categories of this sport, that practiced by people in wheelchairs stands out. Some gaps have been identified in studies of motor coordination in wheelchair athletes, such as which assessment and training procedures could be adopted. The aim of this article was to develop a theoretical reflection of the literature on motor coordination in wheelchair athletes. For this purpose, a search was performed on articles published in scientific journals indexed in specific databases (Pubmed, Scielo and Lilacs). The article was then divided into 03 main sessions: Paralympic sport, wheelchair sports and motor coordination. It is concluded from the publications that motor coordination is fundamental in sports practiced by people in a wheelchair, because the parathlete needs good motor coordination to perform the movements efficiently.